Positive electrode material, preparation method thereof and secondary battery

By modifying the coating on the secondary particles of the positive electrode material of the lithium-ion battery, the problem of insufficient energy density and cycle stability of the existing positive electrode material is solved, and a higher compaction density and lithium ion migration rate are achieved, thereby improving the overall performance of the battery.

CN119742343APending Publication Date: 2025-04-01BTR (JIANGSU) NEW MATERIAL TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411934833.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The specific capacity and energy density of existing lithium-ion battery positive electrode materials are low, which cannot meet the needs of new energy vehicles and other applications.

Method used

The secondary particles modified by the coating are used as the positive electrode material. The secondary particles are composed of multiple primary particles. The coating rate of the coating on the surface of the primary particles is controlled between 4% and 20%, and a layered structure is formed through the sintering process.

Benefits of technology

It improves the compaction density and cyclic stability of the cathode material, enhances the lithium ion migration rate, and improves the energy density and Coulomb efficiency of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742343A_ABST
    Figure CN119742343A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material, a preparation method thereof and a secondary battery. The positive electrode material comprises secondary particles and a coating, the secondary particles comprise a plurality of primary particles, the coating at least partially coats the surfaces of the primary particles, and the coating rate of the coating on the surfaces of the primary particles is 4-20%. The positive electrode material provided by the invention has relatively high energy density and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery positive electrode materials, and in particular to a positive electrode material, a preparation method thereof, and a secondary battery. Background Art

[0002] At present, lithium-ion batteries are widely used in the field of new energy vehicles. The positive electrode materials in lithium-ion batteries are LiCoO2, LiMn2O4, LiFePO4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2 and other materials have low specific capacity and low energy density, and their single-charge mileage is short, which cannot meet the needs of the majority of automobile consumers. Therefore, it is urgent to further improve the energy density of lithium-ion batteries, and the development of positive electrode materials with higher specific energy is the key to improving the energy density of lithium-ion batteries. Therefore, it is urgent to develop a new type of modified positive electrode material to solve the above problems. Summary of the invention

[0003] In view of this, in order to solve at least one of the above defects, the present application provides a positive electrode material, which improves the energy density and cycle stability of the positive electrode material.

[0004] In addition, the present application also provides a preparation method and a secondary battery using the aforementioned positive electrode material.

[0005] The present application provides a positive electrode material, which includes secondary particles and a coating, wherein the secondary particles include a plurality of primary particles, the coating is at least partially coated on the surface of the primary particles, and the coating has a coverage rate of 4% to 20% on the surface of the primary particles.

[0006] In some embodiments, the coverage rate of the coating on the surface of the secondary particles is 2% to 18%.

[0007] In some embodiments, the general formula of the positive electrode material is: Li 1±x Ni a Co b Mn c M α O 2-β T β , wherein 0≤x≤0.5, 0.2≤a≤0.50, 0≤b≤0.1, 0.50≤c≤0.8, 0<α≤0.5, 0<β≤0.5, M is at least one of Al, Ti, Mg, Zr, Mo, Ce, and T is at least one of P, F, Cl, B, I, S, N, and C.

[0008] In some embodiments, the positive electrode material is measured by X-ray diffraction using Cu-Kα rays, and the positive electrode material has an R-3m crystal structure.

[0009] In some embodiments, Cu-Kα rays are used to perform X-ray diffraction measurement on the positive electrode material, and the unit cell parameter c of the c-axis of the positive electrode material is to

[0010] In some embodiments, the positive electrode material is subjected to X-ray diffraction measurement using Cu-Kα rays, and the value of the unit cell parameter c / a of the positive electrode material is 4.96 to 4.99.

[0011] In some embodiments, the length of the coating is 5 nm to 28 nm, and the width is 3 nm to 20 nm as measured by scanning electron microscopy.

[0012] In some embodiments, the thickness of the coating is 2 nm to 15 nm as measured by transmission electron microscopy.

[0013] In some embodiments, the powder compaction density of the positive electrode material at a pressure of 2T is 2.6 g / cc to 3.0 g / cc;

[0014] In some embodiments, the specific surface area of ​​the positive electrode material is 1.6 m 2 / g to 4m 2 / g.

[0015] In some embodiments, the positive electrode material has a median particle size D50 of 2 μm to 16 μm.

[0016] In some embodiments, the length of the primary particle is 120 nm to 300 nm, the width of the primary particle is 120 nm to 300 nm, and the thickness of the primary particle is 100 nm to 150 nm.

[0017] The present application also provides a method for preparing a positive electrode material, comprising: mixing a precursor, a lithium-containing compound, and a compound containing elements M and T to obtain a mixture, and sintering the mixture at 800°C to 1000°C in an air atmosphere to obtain an intermediate; mixing the intermediate with a compound containing elements M and T, and sintering at 250°C to 550°C in an air atmosphere to obtain a positive electrode material, wherein the positive electrode material comprises secondary particles and a coating, the secondary particles comprise a plurality of primary particles, and the coating is at least partially coated on the surface of the primary particles; the coating has a coverage rate of 4% to 20% on the surface of the primary particles.

[0018] The present application also provides a secondary battery, including a shell, an electrode assembly, and an electrolyte or an electrolyte, wherein the electrode assembly and the electrolyte or the electrolyte are both located in the shell, the electrode assembly includes a separator and a negative electrode plate, and the electrode assembly also includes a positive electrode material.

[0019] In the present application, there are multiple primary particles in the secondary particles, and grain boundaries are formed between the multiple primary particles. The grain boundaries can provide a large number of migration channels for the migration of Li ions, thereby improving the migration rate of lithium ions. The coating is coated on the surface of the primary particles and the coating rate on the surface of the primary particles meets a specific range. The coating modifies the interface of the primary particles in the secondary particles and increases the friction force on the surface of the primary particles, which is beneficial to increase the binding force between the multiple primary particles and improve the compaction density of the primary particles. The density increases, thereby increasing the compaction density of the positive electrode material, which in turn helps to increase the energy density of the secondary battery and improve the coulombic efficiency and specific capacity of the positive electrode material.

[0020] Main component symbols

[0021] Electrode assembly 100 , positive electrode sheet 101 , negative electrode sheet 102 , and separator 103 . BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during discharge.

[0023] Figure 2 This is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during charging.

[0024] Figure 3 This is a scanning electron microscope (SEM) photograph of the positive electrode material of Example 1 of the present application.

[0025] Figure 4 This is a scanning electron microscope (SEM) photograph of a part of the positive electrode material of Example 1 of the present application.

[0026] Figure 5 This is a scanning electron microscope (SEM) photograph of the positive electrode material of Comparative Example 1 of the present application.

[0027] Figure 6 This is a transmission electron microscope (TEM) photograph of the positive electrode material of Example 1 of the present application.

[0028] Figure 7 The capacity retention curve of the button-type half-cells of Example 1 and Comparative Example 1 after 50 cycles at high temperature.

[0029] Figure 8 The voltage drop curves of the button-type half-cells of Example 1 and Comparative Example 1 after 50 cycles at high temperature are shown. DETAILED DESCRIPTION

[0030] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0031] An embodiment of the present application provides a secondary battery, comprising a housing, an electrode assembly and an electrolyte. The electrode assembly and the electrolyte are both located in the housing.

[0032] The outer shell can be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), for example, a soft-pack battery. In other embodiments, it can also be a steel shell battery, an aluminum shell battery, etc.

[0033] See also Figure 1 and Figure 2 The electrode assembly 100 includes a positive electrode sheet 101, a negative electrode sheet 102 and a separator 103. The separator 103 is disposed between the positive electrode sheet 101 and the negative electrode sheet 102. When an electrolyte (not shown) is provided, please refer to Figure 1 During discharge, active ions (such as lithium ions) are deintercalated from the lattice of the negative electrode material of the negative electrode plate 102, pass through the electrolyte through the separator 103, reach the positive electrode plate 101 and are embedded in the lattice of the positive electrode material (such as the lithiated intercalation compound), and generate electrons from the negative electrode plate 102 through the external circuit to the positive electrode plate 101. The reverse movement of the electrons forms an electric current that can be used by electrical appliances. When charging, please refer to Figure 2 , active ions (such as lithium ions) are deintercalated from the lattice of the positive electrode material (such as the lithiated intercalation compound) of the positive electrode plate 101, pass through the isolation membrane 103 through the electrolyte, reach the negative electrode plate 102 and are inserted into the lattice of the negative electrode material.

[0034] In some embodiments, the electrode assembly 100 may be a laminated structure, which is formed by alternately stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102. In other embodiments, the electrode assembly 100 may also be a wound structure, which is formed by stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102 in sequence and then winding them.

[0035] The present application also provides a positive electrode sheet, the positive electrode sheet comprising a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, the positive active material layer comprising a positive electrode material. The positive electrode material comprises secondary particles and a coating, the secondary particles comprise a plurality of primary particles, the coating at least partially coats the surface of the primary particles; the average coating rate of the coating on the surface of the primary particles is 4% to 20%.

[0036] In the present application, there are multiple primary particles in the secondary particles, and grain boundaries are formed between the multiple primary particles. The grain boundaries can provide a large number of migration channels for the migration of lithium ions, thereby improving the migration rate of lithium ions. The coating is coated on the surface of the primary particles and the average coating rate on the surface of the primary particles satisfies 4% to 20%. The coating modifies the interface of the primary particles in the secondary particles, which is beneficial to increase the binding force between the multiple primary particles and improve the compaction density of the primary particles, thereby improving the compaction density of the positive electrode material, which is beneficial to improve the energy density of the secondary battery and improve the coulombic efficiency and specific capacity of the positive electrode material.

[0037] If the average coating rate of the coating on the surface of the primary particles is small, such as less than 4%, there are fewer coatings on the surface of the primary particles, and the binding force between multiple primary particles is small, which affects the compaction of the primary particles, thereby affecting the compaction density, initial efficiency and specific capacity of the positive electrode material. If the average coating rate of the coating on the surface of the primary particles is large, such as greater than 20%, it will affect the specific capacity of the positive electrode material. In some embodiments, the average coating rate of the primary particles coated with the coating can be 4%, 6%, 8%, 10%, 13%, 16%, 18%, 20% or any value within the range composed of any two of the above values.

[0038] In some embodiments, the average coverage of the coating on the surface of the secondary particles is 2% to 18%. The coverage of the coating within the above range is conducive to making the secondary battery have good specific capacity, excellent compaction density and initial efficiency, thereby improving the stability and energy density of the secondary battery.

[0039] If the average coverage rate of the coating on the secondary particle surface is small, such as less than 2%, the secondary particle surface coating is small, which will affect the compaction density, initial efficiency and capacity of the positive electrode material. If the coverage rate of the coating on the secondary particle surface is large, such as greater than 18%, the secondary particle surface coating is large, which will affect the capacity of the positive electrode material. In some embodiments, the average coverage rate of the coating on the substrate can be 2%, 4%, 6%, 8%, 10%, 13%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 80%, 81%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 80%, 81%, 82%, 83%, 8

[0040] 16%, 18% or any value within the range formed by any two of the above values.

[0041] In some embodiments, the coating formed by the coating on the surface of the secondary particles has a thickness of 2nm to 15nm. The thickness of the coating layer is within the above-mentioned suitable range. On the one hand, it can reduce the corrosion of the transition metal Mn in the matrix by the electrolyte, which is beneficial to improve the stability of the positive electrode material; on the other hand, the thickness of the coating layer is within the above-mentioned range, which is beneficial to the transmission of lithium ions and to improve the specific capacity and rate performance of the positive electrode material. In some embodiments, the thickness of the coating layer can be 2nm, 6nm, 8nm, 10nm, 13nm, 15nm or any value within the range formed by any two of the above-mentioned values.

[0042] In some embodiments, the positive electrode material is a lithium-rich manganese-based positive electrode material, and the general formula of the positive electrode material is: Li 1± x Ni a Co b Mn c M α O 2-β T β , wherein 0≤x≤0.5, 0.2≤a≤0.50, 0≤b≤0.1, 0.50≤c≤0.8, 0<α≤0.5, 0<β≤0.5, M is at least one of Al, Ti, Mg, Zr, Mo, Ce, and T is at least one of P, F, Cl, B, I, S, N, and C.

[0043] In the related art, the Mn content in the lithium-rich manganese-based positive electrode material is relatively high, and due to the large ionic radius of manganese ions, the unit cell volume increases, making the compaction density of the positive electrode material low, usually between 2.3g / cc-2.4g / cc, and the first efficiency is low (75% to 82%), the capacity retention rate is also poor, and the accompanying voltage drop is large, and the gas production phenomenon is more obvious, thereby affecting the energy density and cycle stability of the positive electrode material in practical applications. The lithium-rich manganese material in the above-mentioned positive electrode material provided in the present application modifies the interface of the primary particles in the secondary particles through the coating, increases the binding force between multiple primary particles, and improves the compaction density of the positive electrode material, thereby improving the energy density of the secondary battery.

[0044] At the same time, in the present application, the coating on the surface of the primary particles in the positive electrode material, the doping of the element M and the element T also helps to synergistically alleviate the mechanical stress caused by the volume change between the primary grains during the charge and discharge process of the secondary battery, inhibit the generation of crystal cracks inside the primary grains, and alleviate the release of oxygen from the positive electrode material, thereby helping to slow down the structural degradation of the positive electrode material and improve the cycle stability of the positive electrode material. The coating can be used as a sacrificial agent to reduce the reaction of the metal elements in the secondary particles with the electrolyte, improve the stability of the secondary particles, and the anions in the positive electrode material can also react with the electrolyte to improve the stability of the solid electrolyte interface film (SEI film) in the secondary battery and improve the cycle stability of the secondary particles; the coating can also isolate the corrosion of the electrolyte to the secondary particles, alleviate the dissolution of Mn in the secondary particles, improve the voltage drop problem of the positive electrode material, and thus extend the service life of the secondary battery. In the positive electrode material, the anion / yang particle doping lattice formed by the element M and the element T can also improve the rate performance of the positive electrode material. The positive electrode material containing element M and element T is also beneficial to reduce the activation of Li2MnO3, alleviate the loss of irreversible lattice O during the first cycle of charging and discharging of the positive electrode material, and improve the first cycle coulomb efficiency and first cycle discharge capacity of the positive electrode material.

[0045] In some embodiments, x can be 0.1, 0.2, 0.3, 0.4, 0.5, or any value within the range formed by any two of the above values. a can be 0.2, 0.25, 0.30, 0.33, 0.35, 0.40, 0.45, 0.50, or any value within the range formed by any two of the above values. b can be 0.02, 0.04, 0.06, 0.08, 0.10, or any value within the range formed by any two of the above values. c can be 0.50, 0.60, 0.65, 0.67, 0.7, 0.75, 0.8, or any value within the range formed by any two of the above values. α can be 0.01, 0.02, 0.05, 0.10, 0.20, 0.30, 0.40, 0.50 or any value within the range formed by any two of the above values, and β can be 0.01, 0.02, 0.05, 0.10, 0.20, 0.30, 0.40, 0.50 or any value within the range formed by any two of the above values. For example, the positive electrode material can be Li 1.30 Ni 0.35 Mn 0.65 Al 0.01 O 1.7 F 0.3 , Li 1.30 Ni 0.34 Mn 0.66 Mo 0.03 O 1.5 F 0.5 , Li 1.35 Ni 0.30Co 0.05 Mn 0.65 Zr 0.02 O2, etc.

[0046] In some embodiments, the positive electrode material is subjected to X-ray diffraction (XRD) measurement using Cu-Kα rays, and the positive electrode material has an R-3m crystal structure, which can improve the initial efficiency, specific capacity and cycle stability of the positive electrode material.

[0047] In some embodiments, the positive electrode material is subjected to X-ray diffraction (XRD) measurement using Cu-Kα radiation, and the unit cell parameter c of the c-axis of the positive electrode material is to The value of the cell parameter c / a of the positive electrode material is 4.96 to 4.99. The cell parameter c and c / a of the positive electrode material satisfy the above range, which is conducive to improving the diffusion rate of lithium ions, so that the diffusion rate of lithium ions is better, so that the positive electrode material has excellent first efficiency and specific capacity. In some embodiments, the cell parameter c of the c-axis can be Or any value within the range formed by any two of the above values, the ratio of c / a can be 4.96, 4.97, 4.98, 4.99 or any value within the range formed by any two of the above values.

[0048] In some embodiments, the length of the coating measured by scanning electron microscopy is 5nm to 28nm, the width is 3nm to 20nm, and the thickness of the coating measured by transmission electron microscopy is 2nm to 15nm. The above-mentioned coating is an island-shaped coating, and the island-shaped coating can be understood as a granular coating located on the surface of a secondary particle or a primary particle. The island-shaped coating is located in a part of the primary particle and does not completely cover the primary particle. The island-shaped coating is on the primary particle and can also be understood as a protruding structure convexly arranged on the surface of the primary particle. The length, width and thickness of the coating are controlled within a suitable range so that the coating-coated substrate has a specific coating rate, and the size of the coating is also conducive to improving the compaction density and specific capacity of the positive electrode material powder within the above range. In some embodiments, the length of the coating can be 5nm, 7nm, 10nm, 15nm, 18nm, 20nm, 23nm, 25nm, 28nm, or any value within the range formed by any two of the above values; the width of the coating can be 3nm, 5nm, 7nm, 9nm, 12nm, 15nm, 18nm, 20nm, or any value within the range formed by any two of the above values; the thickness of the coating can be 2nm, 3nm, 5nm, 7nm, 9nm, 11nm, 12nm, 13nm, 15nm, or any value within the range formed by any two of the above values.

[0049] It should be noted that the length of the coating refers to the maximum distance between the two ends of the coating in a scanning electron microscope, and the width refers to the maximum distance between the two ends of the coating in a scanning electron microscope in a direction perpendicular to the length of the coating. The thickness of the coating refers to the distance from the edge of the lattice stripes away from the center to the side of the lattice stripes away from the lattice stripes along the direction extending from the center to the surface in a transmission electron microscope (TEM) (e.g. Figure 7 The distance indicated by the double arrows).

[0050] In some embodiments, the powder compaction density of the positive electrode material at a pressure of 2T is 2.6g / cc to 3.0g / cc. A coating is formed on the surface of the primary particles of the positive electrode material in the present application, which can increase the compaction density of the positive electrode material, thereby facilitating the improvement of the energy density of the secondary battery. In some embodiments, the powder compaction density of the positive electrode material at a pressure of 2T can be 2.6g / cc, 2.7g / cc, 2.8g / cc, 2.9g / cc, 3.0g / cc, or any value within the range of any two of the above values.

[0051] In some embodiments, the tap density of the positive electrode material is 2.2 g / cc to 2.5 g / cc. The tap density of the positive electrode material is within the above range, which is beneficial to improving the energy density and cycle performance of the secondary battery. In some embodiments, the tap density of the positive electrode material can be 2.2 g / cc, 2.3 g / cc, 2.4 g / cc, 2.5 g / cc or any value within the range formed by any two of the above values.

[0052] In some embodiments, the specific surface area of ​​the positive electrode material is 1.6 m 2 / g to 4m 2 / g. The specific surface area of ​​the positive electrode material is controlled within the above range, which can reduce the side reactions caused by the secondary particles in the positive electrode material contacting with the electrolyte, thereby improving the cycle stability of the secondary battery; and under the above specific surface area, it is also beneficial for the positive electrode material to have a suitable specific capacity. In some embodiments, the specific surface area of ​​the positive electrode material can be 1.6m 2 / g, 2m 2 / g, 2.6m 2 / g, 3m 2 / g, 3.4m 2 / g, 3.8m 2 / g, 4m 2 / g or any value within the range formed by any two of the above values. In some embodiments, the specific surface area of ​​the positive electrode material can be 1.8m 2 / g to 3.6m 2 / g.

[0053] In some embodiments, the median particle size D50 of the positive electrode material is 2 μm to 16 μm. The particle size of the secondary particles is within the above range, which is conducive to obtaining a positive electrode material with a suitable particle size distribution, and the particle size of the secondary particles is within the above range, which is also conducive to forming a coating layer on the substrate, so that the positive electrode material maintains a higher capacity and is conducive to the transmission of lithium ions, thereby improving the energy density of the secondary battery. Among them, D50 is also called "median particle size", which means that the particles of the positive electrode material are measured from the small particle size in the volume-based particle size distribution to reach a cumulative volume of 50%, that is, the volume of the particles of the positive electrode material smaller than this particle size accounts for 50% of the total volume of the particles of the positive electrode material. In some embodiments, the D50 of the positive electrode material can be 2 μm, 5 μm, 7 μm, 10 μm, 13 μm, 15 μm, 10 μm, 16 μm or any value within the range composed of any two of the above values. In some embodiments, the D50 of the positive electrode material is preferably 3 μm to 12 μm.

[0054] In some embodiments, the secondary particles include a plurality of primary particles, the primary particles are strip-shaped structures, the strip-shaped structures are cuboid structures or cuboid-like structures (such as long cuboids with uneven ends), the length of the primary particles is 120nm to 300nm, the width of the primary particles is 120nm to 300nm, and the thickness of the primary particles is 100nm to 150nm. In a scanning electron microscope of a positive electrode material, the longest distance between the two ends of a primary particle on the same plane is the length; in a direction perpendicular to the length, in the same plane as the length direction, the maximum distance between the two ends of a primary particle is the width. In a direction perpendicular to the length and the width, the distance between the two ends on a plane is the thickness. The length, width and thickness of the primary particles are within the above-mentioned appropriate range, which is conducive to the uniform coating of the coating on the primary particles, and the rectangular primary particles also have a higher specific surface area, which can provide more active sites to facilitate the coating and formation of the coating on the primary particles; at the same time, the coating coating the primary particles of rectangular or quasi-rectangular structure The coating rate is higher than the coating rate of the primary particles with a circular or elliptical cross-sectional shape, which is more conducive to improving the powder compaction density, initial efficiency and specific capacity of the positive electrode material.

[0055] In some embodiments, the length of the primary particles in the positive electrode material can be 120nm, 125nm, 145nm, 165nm, 180nm, 200nm, 230nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm or any value within the range composed of any two of the above values. In some embodiments, the width of the primary particles in the positive electrode material is 120nm, 125nm, 145nm, 165nm, 180nm, 200nm, 230nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm or any value within the range composed of any two of the above values. In some embodiments, the thickness of the primary particles in the positive electrode material is 100nm, 110nm, 120nm, 130nm, 140nm, 150nm or any value within the range composed of any two of the above values.

[0056] The present application also provides a method for preparing a positive electrode material, comprising the following steps:

[0057] S1. Mix a precursor, a lithium-containing compound, and a compound containing elements M and T to obtain a mixture, and sinter the mixture at 800° C. to 1000° C. in an air atmosphere to obtain an intermediate.

[0058] In this step, the general formula of the precursor is: Ni a Co b Mn c (OH)2, wherein 0.2≤a≤0.50, 0≤b≤0.1, 0.50≤c≤0.8, a+b+c=1. The above hydroxide precursor is selected to have a high manganese content. For example, Ni 0.35 Mn 0.65 (OH)2,Ni 0.34 Mn 0.66 (OH)2,Ni 0.30 Co 0.05 Mn 0.65(OH)2. In the scanning electron microscope photo of the precursor, the precursor contains a plurality of spherical particles, the spherical particles are secondary particles, the secondary particles are formed by the accumulation of a plurality of primary particles, and the primary particles in the precursor are nanosheet structures, wherein the length of the primary particles is 0.2 μm to 0.6 μm, and the thickness is 2 nm to 10 nm. The thickness and length of the primary particle nanosheet are within the above range, which is easy to be coated with the coating, and is also conducive to the common phase of element M and element T being uniformly doped in the precursor during the subsequent preparation process, thereby facilitating the obtaining of a uniformly doped positive electrode material. In some embodiments, the length of the primary particles in the precursor may be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, or any value within the range composed of any two of the above values. The thickness of the primary particles in the precursor may be 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, or any value within the range composed of any two of the above values.

[0059] In some embodiments, the particle size D50 of the precursor is 2 μm to 16 μm. The particle size range of the precursor within the above range is conducive to the formation of a positive electrode material of a suitable particle size on the precursor particles, and is conducive to the coating being uniformly coated on the surface of the secondary particles, thereby facilitating the acquisition of uniformly coated island-shaped coatings, improving the compaction density and structural stability of the positive electrode material, thereby improving the energy density and cycle stability of the secondary battery. In some embodiments, the particle size D50 of the precursor can be 2 μm, 3 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, or any value within the range formed by any two of the above values. In some embodiments, the particle size D50 of the precursor is 3 μm to 12 μm.

[0060] In some embodiments, the specific surface area of ​​the hydroxide precursor is 20 m 2 / g to 45m 2 / g, the specific surface area of ​​the precursor is within the above-mentioned suitable range, which is conducive to uniformly doping the common phase of element M and element T in the precursor during the preparation process, thereby obtaining a uniformly doped positive electrode material, which is conducive to improving the overall stability of the positive electrode material. In some embodiments, the specific surface area of ​​the hydroxide precursor can be 20m 2 / g, 22m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g, 38m 2 / g, 40m 2 / g, 43m 2 / g, 45m 2 / g or any value within the range formed by any two of the above values. In some embodiments, the specific surface area of ​​the hydroxide precursor is 22m 2 / g to 38m 2 / g.

[0061] In this step, the compound containing elements M and T may be at least one of MgF2, AlF3, TiCl4, ZrB2, MoS2, and AlN.

[0062] At the above sintering temperature, sufficient air can promote the oxidation of divalent nickel to trivalent nickel, reduce the mixing of Li / Ni cations, and help improve the capacity of lithium-rich manganese-based materials. At the same time, this temperature range is conducive to the formation of layered lithium-rich manganese-based materials without causing material decomposition. The above sintering temperature can be 800°C, 850°C, 900°C, 950°C, 1000°C or any value within the range formed by any two of the above values. The above sintering time can be 6h to 20h. Within this range, a layered lithium-rich manganese-based material and a uniform primary particle coating layer can be effectively formed, thereby taking into account the multiple properties of the positive electrode material and improving the battery performance of the secondary battery.

[0063] In some embodiments, the lithium-containing compound includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate or lithium oxalate. The mixing method of the above three substances can be mechanical mixing, such as using a high mixer or a VC mixer. The mixing time can be 0.3h to 3h, such as 0.3h, 0.5h, 0.7h, 1h, 1.3h, 1.8h, 2h, 2.3h, 3h or any value within the range of any two of the above values. In this mixing process, the mixing temperature can be 10°C to 35°C, such as the temperature can be 10°C, 15°C, 20°C, 25°C, 30°C, 35°C or any value within the range of any two of the above values. The mixing temperature is within this range, which is conducive to full mixing and can prevent the mixed raw materials from having side reactions due to excessive temperature.

[0064] In some embodiments, the intermediate calcined product is a mixture of Ni, Co, Mn, and M in a molar ratio of 1.0 to 1.5 in the lithium content of the lithium-containing compound relative to the total amount of Ni, Co, Mn, and M in the positive electrode material. a Co b Mn c (OH)2 hydroxide and lithium-containing compounds, within this range, can not only reduce the degree of Li / Ni cation mixing, but also prevent excessive residual lithium on the surface of the intermediate sintered product from affecting the processing performance and safety performance.

[0065] The present application also provides a method for preparing a precursor, comprising: preparing a salt solution and an alkaline solution in a reactor, mixing them, and simultaneously adding a complexing agent to react (the mass ratio of the salt solution, the alkaline solution and the complexing agent is 1:1.5:0.8), aging; then washing and drying to obtain a manganese-rich ternary precursor with primary particles in the form of thin flakes.

[0066] In this step of preparing the precursor, process parameters such as reaction stirring rate, reaction temperature and time, pH value, aging time, etc. are controlled.

[0067] In some embodiments, the salt solution can be sulfate, such as NiSO4, MnSO4, and the concentration of the sulfate is 1.0 mol / L to 4.0 mol / L, for example, 1.0 mol / L, 1.5 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or any value within the range formed by any two of the above values.

[0068] In some embodiments, the alkaline solution can be sodium hydroxide, and the concentration of sodium hydroxide is 1.0mol / L to 5.0mol / L, such as 1.0mol / L, 1.5mol / L, 2mol / L, 3mol / L, 4mol / L, 5mol / L, or any value within the range formed by any two of the above values. In some embodiments, the complexing agent can be ammonia water, and the concentration of ammonia water is 0.1mol / L to 0.5mol / L, such as 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, or any value within the range formed by any two of the above values.

[0069] In the above reactor, the reaction temperature is 20°C to 60°C, such as 20°C, 30°C, 40°C, 50°C, 60°C or any value within the range of any two of the above values. The reaction time is 10h to 150h, such as 10h, 25h, 36h, 72h, 96h, 120h or any value within the range of any two of the above values. The pH of the solution reaction is 8 to 12, such as 8, 9, 10, 11, 12 or any value within the range of any two of the above values. The aging time after the reaction is 5h to 30h, such as 5h, 10h, 15h, 20h, 25h, 30h or any value within the range of any two of the above values.

[0070] During the above reaction process, it is necessary to take samples in time to test the particle size. When the particle size and sphericity reach the preset target (such as the particle size reaches 2-16μm and the sphericity is close to spherical), start collecting, washing and drying to obtain a manganese-rich ternary precursor with primary particles in the form of thin flakes.

[0071] S2. The intermediate is mixed with a compound containing elements M and T, and sintered at 250° C. to 550° C. in an air atmosphere to obtain a positive electrode material.

[0072] In step S2, the mass ratio of the intermediate to the compound containing elements M and T is 0.05% to 5%, within this range, so that the elements M and T in the compound containing elements M and T are appropriately doped into the intermediate.

[0073] In the above sintering temperature range of 250°C to 550°C, the intermediate is fully mixed with the compound containing elements M and T and reacts. The sintering temperature can be 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or any value within the range of any two of the above values. The sintering time can be 6h to 12h. Combined with this sintering time, the positive electrode material can effectively form a layered structure and a uniform primary particle coating layer.

[0074] In some embodiments, the intermediate and the compound containing elements M and T can be mixed mechanically, such as using a high mixer or a VC mixer. The mixing time can be 0.3h to 3h, such as 0.3h, 0.5h, 0.7h, 1h, 1.3h, 1.8h, 2h, 2.3h, 3h or any value within the range of any two of the above values. In this mixing process, the mixing temperature can be 10°C to 35°C, such as 10°C, 15°C, 20°C, 25°C, 30°C, 35°C or any value within the range of any two of the above values. The mixing temperature within this range is conducive to full mixing and can prevent the mixed raw materials from having side reactions due to excessively high temperatures.

[0075] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil or nickel foil may be used. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate.

[0076] The positive electrode active material layer also includes a binder and a conductive agent, and the binder is used to bind the positive electrode material particles to facilitate the formation of a film layer, and can also improve the bonding force between the positive electrode material layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to a binder polymer, such as polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, modified polyvinylidene fluoride, modified SBR rubber or polyurethane. In some embodiments, the polyolefin binder includes at least one of polyethylene, polypropylene, polyolefin ester, polyolefin alcohol or polyacrylic acid.

[0077] In some embodiments, the conductive agent includes a carbon-based material, a metal-based material, a conductive polymer, or a mixture thereof. Carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, or carbon fiber; metal-based materials such as metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives.

[0078] Negative electrode

[0079] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.

[0080] The negative electrode current collector includes copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, or any combination thereof.

[0081] The negative electrode current collector includes copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, or any combination thereof.

[0082] The negative electrode active material includes a material that reversibly intercalates / deintercalates lithium ions. In some embodiments, the material that reversibly intercalates / deintercalates lithium ions includes a carbon material. In some embodiments, the carbon material can be any carbon-based negative electrode active material commonly used in lithium-ion rechargeable batteries. In some embodiments, the carbon material includes, but is not limited to: crystalline carbon, amorphous carbon, or a mixture thereof. Crystalline carbon can be amorphous, flaky, flake-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.

[0083] In some embodiments, the negative electrode active material layer includes a negative electrode active material. The specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. In some embodiments, the negative electrode active material includes, but is not limited to: lithium metal, structured lithium metal, natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy or any combination thereof. The silicon-carbon composite refers to a composite containing at least about 5 wt% silicon based on the weight of the silicon-carbon negative electrode active material.

[0084] In some embodiments, the negative electrode active material comprises at least one of artificial graphite, natural graphite, hard carbon, soft carbon, silicon alloy, or silicon oxide.

[0085] When the negative electrode includes a silicon-carbon compound, based on the total weight of the negative electrode active material, silicon:carbon=about 1:10-10:1, and the median particle size Dv of the silicon-carbon compound is 50The negative electrode active material layer may be formed by a method such as evaporation, sputtering, or plating. When the negative electrode includes lithium metal, the negative electrode active material layer may be formed by, for example, a spherical and twisted conductive skeleton and metal particles dispersed in the conductive skeleton. In some embodiments, the spherical and twisted conductive skeleton may have a porosity of about 5% to about 85%. In some embodiments, a protective layer may also be provided on the lithium metal negative electrode active material layer.

[0086] In some embodiments, the negative electrode active material layer may include a binder and optionally a conductive material. The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.

[0087] In some embodiments, the conductive material includes, but is not limited to: a carbon-based material, a metal-based material, a conductive polymer, or a mixture thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0088] In some embodiments, the current collector includes, but is not limited to, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and any combination thereof.

[0089] The negative electrode can be prepared by a preparation method known in the art. For example, the negative electrode can be obtained by mixing an active material, a conductive material, and a binder in a solvent to prepare an active material composition, and coating the active material composition on a current collector. In some embodiments, the solvent may include water, etc., but is not limited thereto.

[0090] Isolation film

[0091] The material and shape of the separator used in the secondary battery of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0092] For example, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be selected.

[0093] A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.

[0094] The binder is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene).

[0095] Electrolyte

[0096] According to some embodiments of the present application, the electrolyte includes an organic solvent, a lithium salt, and optional additives.

[0097] The organic solvent in the electrolyte of the present application may be any organic solvent known in the prior art that can be used as a solvent for the electrolyte. The electrolyte used in the electrolyte according to the present application is not limited, and it can be any electrolyte known in the prior art. The additive of the electrolyte according to the present application can be any additive known in the prior art that can be used as an electrolyte additive. In some embodiments, the organic solvent includes, but is not limited to: ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) or ethyl propionate (EP).

[0098] In some embodiments, the organic solvent includes an ether solvent, for example, at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME). In some embodiments, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), bistrifluoromethanesulfonyl imide lithium LiN(CF3SO2)2 (LiTFSI), bis(fluorosulfonyl)imide lithium Li(N(SO2F)2)(LiFSI), lithium bis(oxalate borate) LiB(C2O4)2 (LiBOB) or lithium di(oxalate borate) LiBF2(C2O4) (LiDFOB). In some embodiments, the additive includes at least one of fluoroethylene carbonate and adiponitrile.

[0099] According to some embodiments of the present application, the secondary battery of the present application includes, but is not limited to: a lithium ion battery. In some embodiments, the secondary battery includes a lithium ion battery.

[0100] The present application also applies secondary batteries to electronic devices to power loads in the electronic devices. The electronic devices of the present application are not particularly limited. In some embodiments, the electronic devices of the present application include, but are not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.

[0101] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.

[0102] Example 1

[0103] In this embodiment, the positive electrode material is prepared according to the following method:

[0104] (1) NiSO4 and MnSO4 were prepared into a 2 mol / L mixed salt solution according to the ratio of Ni:Mn=35:65, NaOH was prepared into a 2 mol / L alkaline solution, and 0.24 mol / L ammonia water was selected as a complexing agent; under the protection of nitrogen atmosphere, the mixed salt solution, alkaline solution and complexing agent were added into a 100 L reactor at a flow rate of 2 L / min to react and obtain a manganese-rich precursor Ni 0.35 Mn 0.65 (OH)2, wherein the stirring speed is 20 rpm, the reaction temperature is 40°C, the pH value is 11, the reaction time is 48 hours, and the aging time is 20 hours. The primary particle length of the precursor is 0.35-0.47 μm, the thickness is 5.5-7.1 nm, the D50 is 10.5 μm, and the specific surface area is 32.1 m 2 / g.

[0105] (2) ① Add a manganese-rich precursor, Li2CO3, and AlF3 into 200 mL of ethanol and stir and disperse them, wherein the molar ratio of the manganese-rich precursor to Li2CO3 satisfies Li / (Ni+Mn)=1.30, and based on the mass of Li2CO3, AlF3 and the precursor, the mass fraction of the F element is 0.5wt%, the stirring rate is 1000rpm, and the stirring time is 30min; the dispersed mixture is placed in a vacuum drying oven for drying, and after the ethanol is completely volatilized, the mixture is moved to a high-temperature box furnace for sintering, wherein the sintering atmosphere is an air atmosphere, the sintering temperature is 900°C, the sintering time is 12h, and the heating rate is 5°C / min; the furnace temperature of the high-temperature box furnace is reduced to about 100°C to obtain a lithium-rich manganese-based oxide Li with an island structure coating 1.30 Ni 0.35 Mn 0.65 Al 0.02 O 1.7 F 0.3 ,.

[0106] ② Then weigh the lithium-rich manganese-based oxide prepared in ① and Al2O3 with D50 = 1 μm (the element Al accounts for 0.1% of the mass of the lithium-rich manganese-based oxide) and add them into a 5L high-speed mixer (stirring rate is 1000 rpm, stirring time is 30 min) and mix them evenly. Then sinter them at 400 ° C for 10 h in an air atmosphere to obtain a lithium-rich manganese-based positive electrode material Li 1.30 Ni 0.35 Mn 0.65 Al 0.08 O 1. 7F 0.3 The thickness of the coating layer is 3.2nm-4.8nm. The secondary particles D50 is 9.8μm and the specific surface area is 2.7m 2 / g, the length and width of the primary particles are 130nm~180nm, and the thickness is 118nm~131nm; the average coverage rate of the primary particles in the finished product is 18.6%, and the average coverage rate of the secondary particles is 16.9%.

[0107] Example 2

[0108] In this embodiment, the positive electrode material is prepared according to the following method:

[0109] (1) NiSO4, CoSO4, and MnSO4 were prepared into a 2 mol / L mixed salt solution according to the ratio of Ni:Co:Mn=30:5:65, and NaOH was prepared into a 2 mol / L alkaline solution. Ammonia water with a concentration of 0.24 mol / L was selected as a complexing agent. The mixed salt solution, alkaline solution, and complexing agent were added into a 100 L reactor at a flow rate of 2 L / min under the protection of a nitrogen atmosphere. The manganese-rich ternary precursor Ni 0.30 Co 0.05 Mn 0.66 (OH)2. The stirring speed is 20 rpm, the reaction temperature is controlled at 40 ° C, the pH value is 10.5, the reaction time is 48 hours, and the aging time is 20 hours. The primary particle length of the precursor is 0.45-0.57 μm, the thickness is 4.5-6.1 nm, the D50 is 8.0 μm, and the specific surface area is 34.3 m 2 / g.

[0110] (2)① Add the manganese-rich ternary precursor, Li2CO3, and CeF4 prepared in the above (1) into 200 mL of ether and stir and disperse, wherein the molar ratio of the manganese-rich ternary precursor and Li2CO3 satisfies Li / (Ni+Mn)=1.30, and based on the mass of Li2CO3, CeF4 and the precursor, the mass fraction of the F element is 0.9wt%, the stirring rate is 1000rpm, and the stirring time is 30min. The dispersed mixture is placed in a vacuum drying oven for drying. After the ethanol is completely volatilized, the mixture is moved to a high-temperature box furnace for sintering, wherein the sintering atmosphere is an air atmosphere, the sintering temperature is 860°C, the sintering time is 24h, and the heating rate is 5°C / min. The temperature of the high-temperature box furnace is reduced to about 100°C to obtain a lithium-rich manganese-based oxide with an island structure coating. Obtain a lithium-rich manganese-based oxide with an island structure coating Li 1.30 Ni 0.34 Mn 0.66 Ce 0.1 O 1.6 F 0.4 .

[0111] ② The lithium-rich manganese-based oxide prepared in ① and MoO3 with D50 = 1 μm (the element Mo accounts for 0.3% of the mass of the lithium-rich manganese-based oxide) were weighed, added into a high-speed mixer (stirring rate of 800 rpm, stirring time of 30 min), mixed evenly, and then sintered at 300 ° C for 10 h in an air atmosphere to obtain a lithium-rich manganese-based positive electrode material Li 1.35 Ni 0.29 Co 0.04 Mn 0.64 Ce 0.1 Mo 0.2 O 1. 6F 0.4 The thickness of the coating layer is 5.1nm-7.3nm. The secondary particles D50 is 7.4μm and the specific surface area is 2.5m 2 / g, the length and width of the primary particles are 115nm~136nm, and the thickness is 122nm~135nm; the average coverage rate of the primary particles in the finished product is 15.3%, and the average coverage rate of the secondary particles is 13.2%.

[0112] Example 3

[0113] The difference from Example 1 is that the concentration of ammonia water in the precursor preparation process in step (1) is 0.48 mol / L. The positive electrode material of this embodiment includes active material Li 1.30 Ni 0.35 Mn 0.65 Al 0.08 O 1.7 F 0.3 The remaining steps are the same as those in Example 1.

[0114] The results of the performance test of the positive electrode material prepared in this embodiment are shown in Table 2.

[0115] Example 4

[0116] The difference from Example 1 is that Al2O3 is not added in step (2). The positive electrode material of this embodiment includes active material Li 1.30 Ni 0.35 Mn 0.65 Al 0.02 O 1.7 F 0.3 The remaining steps are the same as those in Example 1.

[0117] The results of the performance test of the positive electrode material prepared in this example are shown in Table 2.

[0118] Example 5

[0119] The difference from Example 1 is that in step (2), AlF3 is replaced by MgF2. The positive electrode material of this example includes active material Li 1.30 Ni0.35 Mn 0.65 Mg 0.08 O 1.7 F 0.3 The remaining steps are the same as those in Example 1.

[0120] The results of the performance test of the positive electrode material prepared in this example are shown in Table 2.

[0121] Example 6

[0122] The difference from Example 1 is that the sintering temperature in step (3) is 700° C. The positive electrode material of this embodiment includes active material Li 1.30 Ni 0.35 Mn 0.65 Al 0.08 O 1.7 F 0.3 The remaining steps are the same as those in Example 1.

[0123] The results of the performance test of the positive electrode material prepared in this example are shown in Table 2.

[0124] Example 7

[0125] The difference from Example 1 is that the amount of AlF3 added in step (2) is reduced, and the mass fraction of F element is 0.05wt%. The positive electrode material of this embodiment includes active material Li 1.30 Ni 0.35 Mn 0.65 Al 0.009 O 1.97 F 0.03 The remaining steps are the same as those in Example 1.

[0126] The results of the performance test of the positive electrode material prepared in this example are shown in Table 2.

[0127] Example 8

[0128] The difference from Example 1 is that the amount of AlF3 added in step (2) is reduced, and the mass fraction of F element is 0.1wt%. The positive electrode material of this embodiment includes active material Li 1.30 Ni 0.35 Mn 0.65 Al 0.028 O 1.91 F 0.09 The remaining steps are the same as those in Example 1.

[0129] The results of the performance test of the positive electrode material prepared in this example are shown in Table 2.

[0130] Example 9

[0131] The difference from Example 1 is that the amount of AlF3 added in step (2) is increased, the mass fraction of F element is 1.2wt%, and the positive electrode material of the embodiment includes active material Li 1.30 Ni 0.35 Mn 0.65 Al 0.29 O 1.38 F 0.62 The remaining steps are the same as those in Example 1.

[0132] The results of the performance test of the positive electrode material prepared in this example are shown in Table 2.

[0133] Example 10

[0134] The difference from Example 1 is that the amount of AlF3 added in step (2) is increased, and the mass fraction of F element is 3.0wt%. The positive electrode material of this example includes active material Li 1.30 Ni 0.35 Mn 0.65 Al 0.23 O 1.25 F 0.75 The results of the performance test of the positive electrode material prepared in this example are shown in Table 2.

[0135] Embodiment 11

[0136] The difference from Example 1 is that AlCl3 is used instead of AlF3 in step (2), and the mass fraction of Cl element is 0.5wt%. The positive electrode material of this embodiment includes active material Li 1.30 Ni 0.35 Mn 0.65 Al 0.08 O 1.7 Cl 0.3 The results of the performance test of the positive electrode material prepared in this example are shown in Table 2.

[0137] Example 12

[0138] The difference from Example 1 is that in step (2), a small amount of AlCl3 replaces part of AlF3, the mass ratio of AlCl3 to AlF3 is 1:1, and the total added mass fraction of F element and Cl element is 0.7wt%. At the same time, lithium hydroxide replaces lithium carbonate. The positive electrode material of this embodiment includes active material Li 1.30 Ni 0.35 Mn 0.65 Al 0.1 O 1.5 Cl 0.2 F 0.3 The results of the performance test of the positive electrode material prepared in this example are shown in Table 2.

[0139] Comparative Example 1

[0140] The difference from Example 1 is that AlF3 is not added in step (2). The positive electrode material of this comparative example includes the active material Li 1.30 Ni 0.35 Mn 0.65 Al 0.08 O2.

[0141] The results of the performance test of the positive electrode material prepared in this comparative example are shown in Table 2.

[0142] Comparative Example 2

[0143] The difference from Example 1 is that AlF3 and Al2O3 are not added in step (2). The positive electrode material of this comparative example includes the active material Li 1.30 Ni 0.35 Mn 0.65 O2.

[0144] Comparative Example 3

[0145] The difference from Example 1 is that the amount of AlF3 added in step (2) is reduced, and the mass fraction of F element is 0.025wt%). The positive electrode material of this embodiment includes active material Li 1.30 Ni 0.35 Mn 0.65 Al 0.005 O 1.985 F 0.015 The remaining steps are the same as those in Example 1.

[0146] Comparative Example 4

[0147] The difference from Example 1 is that the amount of AlF3 added in step (2) is increased, and the mass fraction of F element is 8.0wt%). The positive electrode material of this embodiment includes active material Li 1.30 Ni 0.35 Mn 0.65 Al 0.31 O 1.12 F 0.88 The remaining steps are the same as those in Example 1.

[0148] The performance of the positive electrode materials prepared in the examples and comparative examples was tested using the following test methods and battery performance test methods.

[0149] Test method:

[0150] 1. Scanning electron microscope test

[0151] The morphology of the positive electrode material was analyzed using a Hitachi (S-4800) electron microscope to obtain its scanning electron microscope image.

[0152] 2. Transmission electron microscopy test

[0153] The positive electrode material was subjected to lattice analysis using a FEI Tecnai G2 F20 (200 kV) transmission electron microscope to obtain its transmission electron microscope image, and then its lattice and the thickness of the coating and the coating layer were analyzed. The thickness of the coating layer was obtained by randomly selecting 50 particles and testing the average thickness of the coating layer of each of the 50 particles (the average thickness of the coating layer of each particle can be obtained by selecting at least 5 different positions of the particle and measuring its thickness, and then calculating the average value), thereby obtaining the average thickness of the 50 particles, and the range composed of the average values ​​of the 50 particles is the thickness range of the coating layer.

[0154] 3. Measurement of powder compaction

[0155] The test was conducted using an American CARVER4350 compaction test instrument at a pressure of 2T with a holding time of 30s.

[0156] 4. Coverage rate of primary and secondary particles

[0157] In a scanning electron microscope, the surface area of ​​any 50 primary particles and the area of ​​the coating coated on the surface of the primary particles are counted, and the surface area of ​​a primary particle is the surface area of ​​a coated primary particle located in the outermost layer of the secondary particles and the area of ​​the coating coated on the surface of this primary particle, and the average coverage rate of a single primary particle is calculated; the surface area of ​​50 secondary particles and the area of ​​the coating on the surface of the secondary particles are counted, where the surface area of ​​all primary particles in the outermost layer of the secondary particles is the surface area of ​​the secondary particles, and the area of ​​the coating on the surface of the secondary particles is calculated to obtain the average coverage rate of the secondary particles.

[0158] Battery performance test

[0159] 1. Use button half-cells to evaluate the electrochemical performance of the prepared positive electrode materials and assemble button half-cells.

[0160] The specific method is as follows: the positive electrode material, SP and polyvinylidene fluoride (PVDF) are weighed in a mass ratio of 90:5:5, NMP is added at a solid content of 50%, and a high-speed disperser is used to adjust the viscous slurry, which is evenly coated on the aluminum foil with a scraper, and then dried in an oven at 80°C, and then rolled and cut into a positive electrode sheet with a diameter of 14 mm. A lithium sheet with a diameter of 16 mm is used as the negative electrode sheet, a Celgard polyethylene PP film is used as a separator, and a carbonate solution of LiPF6 with a concentration of 1 mol / L (DEC / EC volume ratio 1:1) is used as the electrolyte. The assembly is carried out in a glove box filled with argon to obtain a button-type half-cell.

[0161] 2. Capacity, initial efficiency and rate performance test of button half-cell

[0162] The capacity, first efficiency and rate performance of the button half-cell were tested at 25° C. and 2.0-4.55 V using a LAND battery testing system, with the reference capacity set to 230 mA / g.

[0163] Button half-cell capacity test:

[0164] First efficiency test of button half-cell: the button half-cell is charged to 4.55V at 0.1C (cut-off current 0.05C), and then discharged to 2V at 0.1C, and the charging capacity and discharging capacity of the button half-cell at 0.1C are calculated respectively; first efficiency = first week discharge capacity / first week charging capacity.

[0165] Rate performance test: The button half-cell is charged to 4.55V at 1C (cut-off current 0.05C), then discharged to 2V at 1C, then charged to 4.55V at 3C (cut-off current 0.05C), and then discharged to 2V at 3C. The discharge capacity at 1C and 3C rates is calculated respectively. Rate performance = 3C rate discharge capacity / 1C rate discharge capacity.

[0166] 3. Measurement of lithium ion diffusion coefficient

[0167] The lithium ion diffusion coefficient of the button half-cell was tested by PITT, using equipment (CT3000A), with a voltage range of 2.0-4.55V and a current density of 230mAg -1 The charging and discharging time is 8 minutes, and the standing time is 60 minutes.

[0168] 4.1C 50-week capacity retention rate

[0169] Under the condition of 45℃, the charge and discharge voltage range is 2.0V-4.55V. The button half-cell is charged to 4.55V at 1C, and then discharged to 2V at 1C. This is the first week of the cycle. The button half-cell is cycled for 50 weeks in the above manner, and the discharge capacity of the button half-cell in the first and 50th weeks of the cycle is tested to test the battery capacity retention rate. The capacity retention rate of the button battery = the discharge capacity of the 50th cycle / the discharge capacity of the first cycle.

[0170] 5. Voltage drop test

[0171] At 45°C, the button half-cell is charged to 4.55V at 1C, and then discharged to 2V at 1C to test the battery discharge voltage. The voltage drop is the difference between the discharge medium voltage in the first cycle and the discharge medium voltage in the 50th cycle divided by 50 cycles.

[0172] Table 1

[0173]

[0174] Table 2

[0175]

[0176] Table 3

[0177]

[0178] Figure 3 and Figure 4 is a scanning electron microscope image of the positive electrode material of Example 1. Figure 3 and Figure 4 In the process, the primary particles are small particles with a roughly rectangular structure, and multiple primary particles are piled up to form secondary particles, which have a spherical structure. Figure 5 It can be clearly observed that island-shaped coatings are attached to the surface of the primary particles, and the primary particles are arranged closely. The length of the coatings is 5 to 10 nm and the width is 3 to 6 nm.

[0179] Figure 5 This is a scanning electron microscope image of the positive electrode material in Comparative Example 1. Figure 5 In the experiment, the particle surface is smooth without coating, and there are large gaps between adjacent primary particles.

[0180] Figure 6 This is a transmission electron microscope image of the positive electrode material prepared in Example 1. Figure 6 The thickness of the coating layer that can be tested (the thickness indicated by the arrow in the figure) is 3.2-4.8nm.

[0181] exist Figure 7 and Figure 8 Compared with Comparative Example 1, the capacity retention rate and voltage drop performance of Example 1 after 50 cycles are significantly improved.

[0182] It can be seen from Table 1 and Table 2 that, compared with Comparative Examples 1 to 4, the positive electrode materials of Examples 1 to 12 contain both island-shaped coatings and the coatings are within a specific range of coverage on the surface of the primary particles, and the powder compaction density of the positive electrode materials is significantly improved, and the assembled secondary batteries also have good discharge capacity, first efficiency and rate performance, and also improve the cycle capacity retention rate and reduce the voltage drop.

[0183] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A positive electrode material, characterized in that: The positive electrode material comprises secondary particles and coatings, wherein the secondary particles comprise a plurality of primary particles, and the coatings at least partially coat the surfaces of the primary particles; the average coating rate of the coatings on the surfaces of the primary particles is 4% to 20%.

2. The positive electrode material according to claim 1, characterized in that The average coverage rate of the coating on the surface of the secondary particles is 2% to 18%.

3. The positive electrode material according to claim 1, characterized in that The positive electrode material is a lithium-rich manganese-based positive electrode material, and the general formula of the positive electrode material is: Li 1±x Ni a Co b Mn c M α O 2-β T β , wherein 0≤x≤0.5, 0.2≤a≤0.50, 0≤b≤0.1, 0.50≤c≤0.8, 0<α≤0.5, 0<β≤0.5, M is at least one of Al, Ti, Mg, Zr, Mo, Ce, and T is at least one of P, F, Cl, B, I, S, N, and C.

4. The positive electrode material according to claim 1, characterized in that The positive electrode material is subjected to X-ray diffraction measurement using Cu-Kα rays, and the positive electrode material satisfies at least one of the following conditions: (1) The positive electrode material has an R-3m crystal structure; (2) The unit cell parameter c of the c-axis of the positive electrode material is to (3) The value of the unit cell parameter c / a of the positive electrode material is 4.96 to 4.

99.

5. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) The length of the coating is 5 nm to 28 nm and the width is 3 nm to 20 nm as measured by scanning electron microscopy; (2) The thickness of the coating was measured by transmission electron microscopy and found to be 2 nm to 15 nm.

6. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) The powder compaction density of the positive electrode material at a pressure of 2T is 2.6 g / cc to 3.0 g / cc; (2) The specific surface area of ​​the positive electrode material is 1.6 m 2 / g to 4m 2 / g.

7. The positive electrode material according to claim 1, characterized in that The median particle size D50 of the positive electrode material is 2 μm to 16 μm.

8. The positive electrode material according to claim 1, characterized in that The length of the primary particle is 120 nm to 300 nm, the width of the primary particle is 120 nm to 300 nm, and the thickness of the primary particle is 100 nm to 150 nm.

9. A method for preparing a positive electrode material, characterized in that: include: Mixing a precursor, a lithium-containing compound, and a compound containing elements M and T to obtain a mixture, and sintering the mixture at 800° C. to 1000° C. in an air atmosphere to obtain an intermediate; The intermediate is mixed with the compound containing elements M and T, and sintered at 250°C to 550°C in an air atmosphere to obtain the positive electrode material, which includes secondary particles and a coating. The secondary particles include a plurality of primary particles, and the coating is at least partially coated on the surface of the primary particles; the coating has a coverage rate of 4% to 20% on the surface of the primary particles.

10. A secondary battery, comprising a housing, an electrode assembly, and an electrolyte or an electrolyte, wherein the electrode assembly and the electrolyte or the electrolyte are both located in the housing, and the electrode assembly comprises a separator and a negative electrode sheet, characterized in that: The electrode assembly further comprises the positive electrode material according to any one of claims 1 to 8 or the positive electrode material prepared by the preparation method according to claim 9.